Combustion and Emission Characteristics of Ammonia under Conditions Relevant to Modern Gas Turbines. Issue 14 (26th October 2021) - Rocha, Rodolfo C.; Costa, Mário; Bai, Xue-Song
ABSTRACT: Ammonia (NH3 ) is considered a promising alternative fuel, capable of producing energy with zero CO2 emissions. Its combustion, however, poses a series of challenges due to the low reactivity of NH3 and the formation of very high quantities of NOx . This work numerically investigates the combustion and emission characteristics of ammonia in three modern stationary gas turbine concepts, namely (a) lean-burn dry-low emissions (DLE); (b) rich-burn, quick-quench and lean-burn (RQL); and (c) moderate or intense low oxygen dilution (MILD), under operating conditions typical of commercial gas turbines (inlet temperatures of 500 K and pressure of 20 bar). Numerical simulations employing detailed chemical kinetic mechanisms are carried out to study the propagation speed of ammonia, the combustor temperatures, and the emissions of NOx and NH3 . The simulations are first validated against literature NOx data and then the most accurate mechanism is selected. The performance of the different gas turbine engine concepts is subsequently compared based on the results from the selected mechanism. The results show that the lowest emissions are achieved with the RQL and MILD combustion concepts, while the DLE combustion concept only presents acceptable emission values under conditions deemed unstable, where the laminar flame speeds are below 3 cm/s.